The perception of the territory naturalness an application in the bergamo area - Francesco Scarlatti; Giovanni Rabino (European Regional Science Association (ERSA), 2004)
It is very discussed about the sustainability of urban areas. One of the requests of urban sustainability consists in the capability of the city to preserve around itself a good level of naturalness: A sustainable economy reflects an image of its territory that must represent a landscape of agreeable towns, of intact agricultural mosaics and of a large natural areas patrimony. Ours research, starting from the proposal expressed from E. Koomen, J Groen, J Borsboom and H Scholten with the work “Modelling the fragmentation of open space. A framework for assessing the impact of land use change on open space” presented at the ERSA Congress in 2002, intends to find the modality with which the naturalness influences the surrounding areas, the zones where nature and population pressure are not in antithesis and the natural areas that risks to be lost. The goal will be reached applying the concept of “field”. The base idea is that the areas with larger “naturalness” constitute a sort of positive virus that influences the surrounding zones. The GIS-oriented model presupposes the discrete division of the territory and the use of a simple field algorithm applied to an naturalness indicator opportunely studied. The application, for the validation of the model, has been implemented on the Bergamo's province; choosing a territorial scale that allows to do observations and preliminary evaluations at the level of urban planning to locate large infrastructures.
Keywords: 330